Analysis of Account Dayfiles for the CDC 6400 Computer Under NOS - Ng, Hok-Nam (My University, 1979)
System performance evaluation is an on-going task for computer system management personnel in order to fine-tune the system operations. One of the evaluation aids that is readily available for the CDC 6400 computers is the job accounting dayfile maintained by the operating system NOS. A set of three programs in FORTRAN has been developed to analyze the dayfile with a view to evaluating the system performance. Program PHASEl prepares the dayfile for analysis. Program PHASE2 creates a job summary file with information on system resources utilization by each job. Program PHASE3 analyzes the job summary file by evaluating various parameters characterizing the system workload and performance at regular time intervals. The results are displayed in tabular and graphical forms. Test results from the analysis of a limited number of dayfiles are discussed.
Keywords: CDC 6400; Account Dayfiles; NOS; Computer